EMOTIONAL INTELLIGENCE OF MANAGER AND SALESPERSON CREATIVITY - Jain, Neha; Nim, Dheeraj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The front-line workforce plays a critical and responsible role in personal selling because they directly interact with customers and correspond to the face of the company. business environment is highly competitive and rapidly changing in today’s scenario. Organizations should take maximum advantage of their creativity and potential to prosper or even for their survival. The requirement to improve innovative performance for long-term success is feasibly true in the selling occupation, where individual and organizational success depends on presenting ground-breaking and constructive solutions for customers. The current research shows that a leader’s emotional intelligence positively supports workers’ creative performance and extends by exploring how a sales representative’s emotional intelligence influences his or her creativity and key work outcomes. The conclusions are conferred in terms of hypothetical and professional implications. Limitations and suggestions for future research are also offered.